Determinan Minat Mahasiswa Dalam Menabung Di Bank Syariah (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnin Islam UIN Sultan Maulana Hasanudin Banten - Fadhila Meliyanti; Wiwi Widia Argita; Darul Arqom; Wahyu Hidayat (KOLONI, 2023)
This study aims to analyze the Determinants of Student Interest in the Faculty of Economics and Islamic Business in Using Islamic Banks. This study uses a quantitative approach by distributing anghket to respondents as many as 30 students of the Faculty of Economics and Islamic Business. Then the collected data were analyzed by descriptive and inferential statistical methods. The results showed that the factors that influence the interest of FEBI UIN SMH Banten students in saving at Islamic banks, which cannot be separated from two factors, namely service and product quality. The development of Islamic Banks can be seen clearly observing that the Bank operates by implementing a system based on sharia principles that is able to answer the needs of customers. The development of Islamic Bank itself is inseparable from this behavior, customers who believe in the quality and quantity of products offered by the bank. Behavior reflects the satisfaction received as a customer to the bank as a place to collect and manage their funds. Customer behavior is a reflection of customer behavior which expresses the feelings received by the services they receive as customers. Keywords: Knowledge, Service Quality and Interest in Saving